Survival Outcomes in Asymptomatic Patients With Normal Conventional Imaging but Raised Carcinoembryonic Antigen Levels in Colorectal Cancer Following Positron Emission Tomography-Computed Tomography Imaging. (14th October 2016) - Khan, Khurum; Athauda, Avani; Aitken, Katharine; Cunningham, David; Watkins, David; Starling, Naureen; Cook, Gary J.; Kalaitzaki, Eleftheria; Chau, Ian; Rao, Sheela
Abstract : Background: This study had two aims: (a) to evaluate the utility of fluorine 18-fluorodeoxyglucose (FDG) positron emission tomography (PET)-computed tomography (CT) in detecting occult disease recurrence with raised carcinoembryonic antigen (CEA) and (b) to establish the prognostic effects of early detection of disease recurrence in patients with colorectal cancer (CRC). Patients and Methods: Clinico-pathological data were obtained from all consecutive patients undergoing CRC surveillance from 2004 to 2010 who had an elevated CEA level (>3 ng/mL in nonsmokers, >5 ng/mL in smokers) but normal or equivocal conventional investigations. Histopathological confirmation or a minimum of 12 months' clinical and radiological follow-up were required to ascertain disease relapse. Results: A total of 1, 200 patients were screened; of those, 88 (59% men; mean age, 66 years [SD, 9.6]) eligible patients (67 with normal and 21 with equivocal results on conventional investigations) were identified. Recurrent disease was detected in 56 of 88 patients (64%). The sensitivity of FDG PET-CT to detect recurrence was 49 of 56 (88%; 95% confidence interval [CI], 76%–95%) and specificity was 28 of 32 (88%; 95% CI, 71%–97%). Twenty-seven of 49 (55%) patients with PET-CT-detected relapsed disease were deemed eligible for further curative therapy; 19 (70%) went on to receive potentially curative therapy. The median time to progression (8.8 months [interquartile range (IQR), 4.5–19.1 months] vs. 2.2 months [IQR, 0.7–5.6]), median overall survival (39.9 months [IQR, 23.6–65.4 months] vs. 15.6 months [IQR, 7.3–25.7 months]), and 5-year survival (36.8% [95% CI, 16.5%–57.5%] vs. 6.1% [95% CI, 1.1%–17.6%]; p ≤ .001) were higher in patients who received potentially curative therapy than in those who received noncurative therapy. Conclusion: FDG PET-CT is a highly sensitive and specific tool for the detection of occult CRC recurrence. In >50% of patients, recurrent disease may still be potentially amenable to curative therapy. Long-term survival can be achieved in such patients. Abstract : This study showed that fluorine 18-fluorodeoxyglucose positron emission tomography–computed tomography was highly sensitive and specific for the detection of occult recurrence of colorectal cancer in patients with a raised carcinoembryonic antigen level and normal results on conventional investigations.